Determinants of Energy Consumption for Asean-4 Countries: Indonesia, Malaysia, Philippines, and Thailand - Melissa, Goh Enn Xia (Universiti Malaysia Sarawak, (UNIMAS), 2022)
The aim of this study is to investigate the determinants of energy consumption for selected 4 ASEAN countries: Indonesia, Malaysia, Philippines, and Thailand by incorporating panel data from year 1991 to year 2020. The determinants energy consumption of ASEAN countries is gross domestic product, carbon dioxide emissions and total trade. EViews was the software used to regress the panel data. The data was analysed through the deployment of panel unit root test and panel cointegration in determining the determinants of energy consumption of the selected countries. The empirical findings from panel cointegration, Pooled Mean Group (PMG) method, and Fully Modified Ordinary Least Square (FMOLS) estimators in checking the robustness of the results. Granger Causality Test was used to check the causality relationship between the variables. The study founded that the relationship between the energy consumption and economic growth provides evidence on the hypothesis that economic development leads on decreasing levels of energy use with higher environmental quality issues and will influence the trade activities while assist the strategy planning in energy investment.